2006
DOI: 10.1007/bf02956778
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wines, grape juices and cranberry juices forAlternaria toxins

Abstract: Sixty six samples of red and white wine from Ontario (VQA), British Columbia (VQA), Québec ("vins artisanaux"), imported wines (from Italy, South America and USA) and Canadian and US grape and cranberry juices were analysed for theAlternaria mycotoxins alternariol (AOH) and alternariol monomethyl ether (AME). After cleanup on aminopropyl SPE columns, AOH and AME were initially determined by reversed phase LC with UV detection. Positive sample extracts were re-analysed by LC-tandem negative ion electrospray mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 11 publications
4
63
0
1
Order By: Relevance
“…In North America, AOH, AME and TeA were analysed in 120 food samples of fruit juices and wines (Scott et al, 1997(Scott et al, , 2006Lau et al, 2003;Abramson et al, 2007). Regarding the studies of Scott et al (2006) and Lau et al (2003), only the results obtained by LC-MS or LC-MS/MS are reported in Appendix B Table B1.…”
Section: Previously Reported Occurrence Results Of Alternaria Toxins mentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, AOH, AME and TeA were analysed in 120 food samples of fruit juices and wines (Scott et al, 1997(Scott et al, , 2006Lau et al, 2003;Abramson et al, 2007). Regarding the studies of Scott et al (2006) and Lau et al (2003), only the results obtained by LC-MS or LC-MS/MS are reported in Appendix B Table B1.…”
Section: Previously Reported Occurrence Results Of Alternaria Toxins mentioning
confidence: 99%
“…Regarding the studies of Scott et al (2006) and Lau et al (2003), only the results obtained by LC-MS or LC-MS/MS are reported in Appendix B Table B1.…”
Section: Previously Reported Occurrence Results Of Alternaria Toxins mentioning
confidence: 99%
“…Alternariol and alternariol methyl ether were found in red wine bought in Canada (Scott et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…The ability of A. alternata to produce several different mycotoxins renders it interesting for mycotoxicologists (Scott et al 2006). Nevertheless, other Alternaria species are also able to produce mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the occurrence of AOH, AME and TA has been reported in wine [46][47][48], the presence of Alternaria isolates in the vineyard, harvest or post-harvest could not be correlated with the presence of mycotoxins in wine due to the lack of studies.…”
Section: Discussionmentioning
confidence: 95%